2017
DOI: 10.1016/j.jascer.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

High pressure growth and electron transport properties of superconducting SmFeAsO1−xHx single crystals

Abstract: We report the single crystal growth and characterization of the highest T c ironbased superconductor SmFeAsO 1−x H x . Some sub-millimeter-sized crystals were grown using the mixture flux of Na 3 As + 3NaH + As at 3.0 GPa and 1473 K. The chemical composition analyses confirmed 10% substitution of hydrogen for the oxygen site (x = 0.10), however, the structural analyses suggested that the obtained crystal forms a multidomain structure. By using the FIB technique we fabricated the single domain SmFeAsO 0.9 H 0.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…under-doped regime) 10 , and LiFeAs 8 . For all OP samples, on the other hand, the temperature-dependent ρ c (T ) was metallic, which differs from the reports on PrFeAsO 0.7 12 , SmFeAs(O,F) 13 and SmFeAsO 0.9 H 0.1 14 single crystals. To identify the reason of this difference, it is desired to measure ρ c (T ) using NdFeAs(O,F) single crystals.…”
Section: Resultscontrasting
confidence: 99%
“…under-doped regime) 10 , and LiFeAs 8 . For all OP samples, on the other hand, the temperature-dependent ρ c (T ) was metallic, which differs from the reports on PrFeAsO 0.7 12 , SmFeAs(O,F) 13 and SmFeAsO 0.9 H 0.1 14 single crystals. To identify the reason of this difference, it is desired to measure ρ c (T ) using NdFeAs(O,F) single crystals.…”
Section: Resultscontrasting
confidence: 99%
“…1d). It is reported that the c-axis lattice parameter decreases with increasing hydrogen content x in LnFeAsO1-xHx [7,10,11] with a rate of Dc/Dx~-2-3×10 -3 Å/at.%. The lattice parameter c of our NdFeAs(O,H) film determined by x-ray diffraction (XRD) was 8.437±0.003 Å, which also supports the lattice shrinkage due to hydrogen doping although the value was slightly shorter than the average value evaluated from TEM.…”
Section: Microstructurementioning
confidence: 99%
“…The growth of LnFeAs(O,H) opens new opportunities to explore how heavily electron doping influences the superconducting properties. However, most of the studies have been carried out on polycrystals [7,8] or tiny single crystals [10], on which measurements of the transport critical current density are rather complicated. The successful growth of LnFeAs(O,H) epitaxial thin films gives a great opportunity to explore the intrinsic physical properties by electrical transport measurements especially for critical current characteristics, since thin films are the ideal platform for such investigations.…”
mentioning
confidence: 99%
“…Although small size crystals with maximum at ~400 μm were reported recently [14], it is very difficult to grow enough large-size single crystals of H-doped Sm1111, which restricts further detailed investigations on the superconducting mechanism and the electronic band structure by experimental methods such as angle-resolved photoemission spectroscopy.…”
Section: Introductionmentioning
confidence: 99%